Usability evaluation of orientation techniques for medical image analysis using tabletop system - Madni, T.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Tabletop systems support simultaneous multi-user multi-touch interaction to select and manipulate digital contents such as text, images, and videos directly and in a natural way. These digital contents require the proper orientation to perform co-located collaborative tasks. To achieve this, some orientation techniques are also proposed in different domains. But, the orientation issue is still reported for collaborative medical image analysis around tabletop systems. The presence of the inappropriate digital content-orientation on tabletop displays limits the collaborative medical image analysis. It also decreases the visibility, accessibility and readability of digital contents during co-located collaborative interaction. This paper presents a user study to evaluate usability of the two different orientation techniques for diagnosing and monitoring of medical images from the user perspective. Subsequently, the comparative analysis of those techniques is presented and discussed based on the obtained data. The findings suggest that the manual-orientation technique provide better usability as compared to the global-orientation technique for diagnosing and monitoring the medical images. Finally, the future work is suggested based on the obtained findings to enhance the usability. Â© 2016 IEEE.